Classification and Characteristics of Students Groups Using Change of Attitude in Class for Creating Slides to Present Product (Asian Education Studies, 2016)
The creation of product presentation slides using PowerPoint was implemented in order to ensure that students acquire the knowledge and information literacy required to use computers. Students created slides presenting products in which they were interested, inserting animation and recording narration. This class combined evaluation and revision activities. Along with enhancing computer skills, awareness relating to a variety of skills required for problem solving were enhanced in an attempt to cultivate independent thinking skills. In particular, the aim was not only to enhance PowerPoint skills, but also to improve expressiveness, planning ability and ability to make proposals. This paper reports the contents and change of attitude in the class to create product presentation slides. Principal component analysis and cluster analysis are conducted using elongation in assessed values. As a result, students are classified in some groups and characteristics of each group is reported. Important categories for group are extracted through discriminant analysis. Significance difference test for change of awareness related to abilities peculiar to this class will be reported. Finally it is considered those results.